(3GdebQH aj GdfMhs - (3CHh GdMSf Ydj Hf eDef Hf YUahQ GdGTHjdjs ((3GdbGgQI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi de fSJaJM HCaVd ef CSeg cdGe hHYO aEfg deG cGf Yde GdYQHjI ef CLd GdYdhe bOQkG hCYXegG NWQkG EP Hg Jbhe ddEfSGf OeGFI HGH JHjjf GdcdGe hCLRGFg GdcdGe EUWdGMkG gh GddaX GdeQcH hLhOkG s
(3BNQgG (B:s
(3agPg CUfGa GdVQGjQ hbO JbOe PcQ CcKQgG eaUdkG ai JVGYja GdCHhGH aCZfi Pdc Yf EYGOJg gfG hjLhR GdbjGS Ydi cKQI ESJYeGdg ef Pdc heGde jcKQ adG SHjd Edi GdbjGS Ydjg hGddg CYde Je cJGH GdebQH JUfja GdEeGe GdChMO CHj GdMSf Ydi Hf eDef Hf YUahQ GdMs
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs